Evaluación de la calidad de la educación universitaria: modelos vigentes - Bermeo Ramírez, Carmen Rosa (2011)
The article offers a selection of the most adequate Ouality concepts far the educational task, as well as fundamental characteristics to be taken into consideration far every educational offerwith mínimum requirements ofquality.Likewise, several models to evaluate quality in education in universities are shown stressing the most used models in Latin America with the hope to give ideas far designing, elaborate and used the most convenient evaluative model farevery institution.